The impact of cognitive impairment on upper body dressing difficulties after stroke: a video analysis of patterns of recovery. Issue 1 (5th January 2004) - Walker, C M; Sunderland, A; Sharma, J; Walker, M F
Abstract : Objective: to study the underlying cognitive deficits influencing a stroke patient's ability to relearn to dress. The aim was to investigate how recovery had occurred and whether the nature of cognitive impairment was the reason for persistent dressing problems. Methods: the dressing performance of 30 stroke patients was compared at the sub-acute stage and three months later. Standardised cognitive and physical tests were carried out, together with a video analysis of patients putting on a polo shirt. Results: thirteen patients with preserved power in the upper limb used both arms to put on the shirt. Despite visuospatial impairment or apraxia in some cases, all were successful given sufficient time. Out of 17 patients with arm paresis, 12 were dependent putting on the shirt. Amongst the five who were independent, significantly fewer cases of cognitive impairment were seen on tests for apraxia (p<0.05) and visuospatial perception (p<0.05). Video analysis confirmed the importance of cognitive problems such as neglect or apraxia. Three patients who failed shirt dressing showed neglect or apraxia at follow up and had persistent arm paresis. Test failures also occurred amongst those who were independent. Discussion: cognitive impairment affected patients attempting to relearn to dress with one hand, but did not affect patients who used both hands. The three patients who remained impaired on cognitive tests at follow up were unable to adapt or learn any compensatory strategies. The influence of cognition on a person's ability to learn compensatory strategies has implications for the design of rehabilitation therapies.